2018
DOI: 10.1038/s41598-018-36169-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting coral dynamics through climate change

Abstract: Thermal-stress events are changing the composition of many coral reefs worldwide. Yet, determining the rates of coral recovery and their long-term responses to increasing sea-surface temperatures is challenging. To do so, we first estimated coral recovery rates following past disturbances on reefs in southern Japan and Western Australia. Recovery rates varied between regions, with the reefs in southern Japan showing more rapid recovery rates (intrinsic rate of increase, r = 0.38 year−1) than reefs in Western A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Most frequently, ordinary, autonomous differential equations (i.e. ODEs) are employed (Wolanski et al 2004, Riegl & Purkis 2009, Bas-kett et al 2010, Melbourne-Thomas et al 2011, van Woesik et al 2018.…”
Section: Differential and Difference Equation Models (Dems)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most frequently, ordinary, autonomous differential equations (i.e. ODEs) are employed (Wolanski et al 2004, Riegl & Purkis 2009, Bas-kett et al 2010, Melbourne-Thomas et al 2011, van Woesik et al 2018.…”
Section: Differential and Difference Equation Models (Dems)mentioning
confidence: 99%
“…DEMs or MPMs). While ODEs and DEs have been widely used in the analysis of coral cover (Mumby et al 2007, van Woesik et al 2018, only a few applications address coral size distributions (Sebens 1982, Riegl & Purkis 2009, Riegl et al 2013, Baskett et al 2014. The strengths of DEMs are their flexibility in allowing precise statements with regards to the population variables of interest.…”
Section: Differential and Difference Equation Models (Dems)mentioning
confidence: 99%
“…Specific reef recovery responses to past thermal exposure should ideally inform any prediction of future ecological responses to projected climate exposure (Donner and Carilli 2019). However, to date, studies by Ortiz et al (2014), Van Woesik et al (2018), and Wolff et al (2018 are unique examples of ecological responses to accumulated thermal stress (eg DHWs/DHMs) or monthly SST. These measures account for shorter term thermal extreme events causing coral bleaching and mortality, but cannot represent the effects of protective pre-bleaching exposure (Ainsworth et al 2016), diurnal SST variability (Safaie et al 2018), peak SST, thermal history, and duration of cool periods (McClanahan et al 2019).…”
Section: Linking Climate-change Exposure To Ecological Responses and Adaptive Capacitymentioning
confidence: 99%
“…Currently, these responses to multiple climatic disturbances are difficult to quantify because of the lack of long-term data and presence of multiple factors that affect coral reef sensitivity. Even though such detailed data collection is costly and time consuming, long-term datasets are increasingly needed to better understand the response of corals to climate stressors (Van Woesik et al 2018;Darling et al 2019;Donner and Carilli 2019).…”
Section: Linking Climate-change Exposure To Ecological Responses and Adaptive Capacitymentioning
confidence: 99%
“…Serious pollution emissions would lead to a reduction in biodiversity and increase in sediment and nutrient input, thereby increasing the risk of eutrophication in offshore waters and damaging marine ecosystems. Woesik, et al [18] found that when sudden, short-term climate oscillations occur, especially in the case of El Niño events, coral reef ecosystems are greatly damaged by exposure to abnormally high temperatures, and the resilience of coral reefs is also reduced due to the low cover of the damaged coral populations. Chin, et al [19] integrated regional and national report information and found that most coral reefs in the Pacific Ocean remain healthy as a whole, but, in some areas, coral reefs were suffering varying degrees of damage due to environmental and human factors.…”
Section: Introductionmentioning
confidence: 99%